Antimony Doped Tin Oxide Thin Films: Co Gas Sensor - P.S. Joshi; S.M. Jogade; P.A. Lohar; D.S. Sutrave (Журнал нано- та електронної фізики)
Tin dioxide (SnO2) serves as an important base material in a variety of resistive type gas sensors. The widespread applicability of this semicoducting oxide is related both to its range of conductance variability and to the fact that it responds to both oxidising and reducing gases. The antimony doped tin-oxide films were prepared by spray pyrolysis method. The as-deposited films are blackish in colour. Addition of antimony impurity showed little increase in the thickness. The X-ray diffraction pattern shows characteristic tin oxide peaks with tetragonal structure. As the doping concentration of antimony was increased, new peak corresponding to Sb was observed. The intensity of this peak found to be increased when the Sb concentration was increased from 0.01 % to the 1 % which indicates the antimony was incorporated into the tin oxide. For gas sensing studies ohmic contacts were preferred to ensure the changes in resistance of sensor is due to only adsorption of gas molecule. The graph of I-V shows a straight line in nature which indicates the ohmic contact. The sensitivity of the sensor for CO gas was tested. The sensitivity of antimony doped tin oxide found to be increased with increasing Sb concentration. The maximum sensitivity was observed for Sb = 1 % at a working temperature of 250 °C.